2014
DOI: 10.1038/pr.2014.202
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-derived exosomal miRNAs: a novel mechanism for obesity-related disease

Abstract: BackgroundObesity is frequently complicated by comorbid conditions, yet how excess adipose contributes is poorly understood. Although adipocytes in obese individuals induce systemic inflammation via secreted cytokines, another potential mediator has recently been identified (i.e. adipocyte-derived exosomes). We hypothesized that adipocyte-derived exosomes contain mediators capable of activating end-organ inflammatory and fibrotic signaling pathways.MethodsWe developed techniques to quantify and characterize ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
230
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(253 citation statements)
references
References 38 publications
(49 reference statements)
8
230
0
1
Order By: Relevance
“…Adipocytes from obese individuals actively shed miRNAcontaining exosomes (35), which may affect signaling in nearby cells. We have previously shown that exosomes secreted by preadipocytes contain high levels of miR-140 and that treatment with shikonin can induce high levels of miR-140 in preadipocyte exosomes (23).…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes from obese individuals actively shed miRNAcontaining exosomes (35), which may affect signaling in nearby cells. We have previously shown that exosomes secreted by preadipocytes contain high levels of miR-140 and that treatment with shikonin can induce high levels of miR-140 in preadipocyte exosomes (23).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are membrane vesicles that carry a cargo of proteins, lipids and nuclear acids, which may differ based on adipogenic stages and/or under pathological conditions [120,121,122]. Adipocyte-secreted exosomes are demonstrated to contain specific transcripts (such as adiponectin [123] and aP2 [124]) and miRNAs [119,99], which are transported into recipient cells and are involved in modulating gene expression as well as energy metabolism.…”
Section: Excessive Adipose Tissuementioning
confidence: 99%
“…Adipocyte-secreted exosomes are demonstrated to contain specific transcripts (such as adiponectin [123] and aP2 [124]) and miRNAs [119,99], which are transported into recipient cells and are involved in modulating gene expression as well as energy metabolism. Several studies demonstrated that adipocyte derived exosomes mediate cell-cell communication that might play a role in controlling lipogenesis and cell size [121], obesity related disease [120] and nonalcoholic fatty liver disease [125]. It is possible that exosomes from bone marrow adipose tissue under osteoporotic conditions carry different cargo to affect the osteoblastic/adipocytic fate of bone marrow MSCs.…”
Section: Excessive Adipose Tissuementioning
confidence: 99%
“…Few studies have focused on ad-exos in obesity, although their function and content are modified. For instance, they are implicated in insulin resistance (11) and their miRNAs mediate inflammation and fibrosis (12).…”
Section: Introductionmentioning
confidence: 99%